References to the abused body in the theatrical actor’s performance (Al-Academy, 2024)
The names and concepts varied in defining the art of the actor as one of the most important tools upon which the theatrical process is based, along with other elements of the show, to be an explainer, imitator, imitator, and embodiment of the role on stage, in the presence of the audience, which is an important element for the success of the theatrical game. However, in our research, we replace the term (actor (B) with (the performer), who formulated a different performance structure by demolishing the actor’s requirements of text and the fourth wall, moving away from analyzing and embodying the character, relying only on his physical body, to establish a relationship different from what was known in the past, whose tools are (the body The violent person is a performativity type that dialogues with human instincts and arouses his ferocity derived from his natural composition within the living environment, using hurtful tools to create a ritual space between him and the recipient, playing on his senses and feelings to produce new meanings and connotations that destroy old constants to formulate a meaning through the body of the violent performer within a complex and complex performance process. It is based on intellectual, sensory, and mental senses. It is a process that changes according to the concepts and performance systems that operate according to the context of demolition and construction. Thus, it seeks to formulate an artistic space. Everything it contains is subordinate to the body of the real performer, who has no features. The character that the actor performs and replaces it with his own characteristics, in order to affect the meaning derived from such performances that destabilize the previous constants of the signifier and the signified and generate other meanings.This was made clear through the research chapters, represented by the first chapter (methodological framework) and the second chapter, which consisted of the first section (the social and psychological concepts of the abused body) and the second section (the abused body in theatrical performance), leading to the third chapter (research procedures), which included an analysis of the play (Autumn). Chapter Four (Results and Conclusions) and we mention some of them:1- Violated bodies were able to demonstrate their ability to destroy and build through their psychological and physiological transformations. At times, they are (reassuring, strong, and balanced) and at other times we find them (fearful, weak, almost dissociative).2- The ability of the (Iraqi actor) to create approaches between (re-presenting the text) and (self-torture performances) by penetrating the elements of (the actor, the text, and the stage).